Generator Magnet Permanen Sebagai Pembangkit Listrik Putaran Rendah - Prasetijo, Hari; Ropiudin, Ropiudin; Dharmawan, Budi (Dinamika Rekayasa, 2012)
Development renewable energy as electrical energy need to be followed by provision of low speed generator, especially for small-scale use of alternative energy. This study discusses the design of low speed synchronous generator using permanent magnets for producing magnetic flux in the rotor. Stator coils are designed so that on the rotation of 500 rpm generator can produce 5 watts output power at 3 phase voltage 12 Vac.